Factores Determinantes del Costo de los Departamentos en la Ciudad de Loja, año 2015 - Briceño Reyes, Ruth Alexandra (2016)
Due to the heterogeneity of good housing, there are significant differences in market prices that do not allow proper measurement, hence derives uncertainty and information asymmetry, hampering good decision-making of the participants in this market. Whereas the housing has been declared by the United Nations Organization as a fundamental element to ensure the social welfare of individuals; it proposed to realize the present entitled investigation: "Determinants of the cost of apartments in the city of Loja, 2015". The general objective of the investigation was to determine the factors that influence the price of apartments in the city of Loja by a correlation analysis and hypothesis testing; and thus provide input to the real estate market participants to enable them proper decision-making, and reduced uncertainty both as information asymmetries in the market. The study population was represented by the new and used departments available for sale in the city of Loja. The investigation was descriptive, in which the scientific, inductive, deductive and analytical method was used. After analyzing the results of the investigation, it was determined that the average price of apartments amounted US$ 102.000, with the characteristics total area of the department, number of bathrooms, number of bedrooms, presence of separate dining room, holding water heater, geographic location and seniority, factors that were coupled to an econometric model of multiple linear regression , which allowed the calculation of the implicit marginal